Promising Polymeric Buccoadhesive Bilayered Tablets Releasing Valsartan: Effect of Gel strength on Drug Release - Abu-Huwaij, Rana (Jordan Journal of Pharmaceutical Sciences, 2018)
The objective of the present study was to develop buccal bilayered controlled release tablets in order to overcome the poor oral bioavailability of valsartan. They were prepared by direct compression. Various types and amounts of mucoadhesive polymers were investigated. The tablets were evaluated for weight variation, thickness, hardness, friability, surface pH, mucoadhesive strength, swelling index, in vitro drug release, and permeation to optimize the formulation. The tablets containing carbopol 934, hydroxypropyl methyl cellulose (HPMC), sodium alginate in the ratio of 3:2:1, respectively, exhibited a promising mucoadhesive bilayer tablets. They had acceptable physical properties, maximum mucoadhesive strength of 62.68 ± 0.91 g/cm2, and a zero order controlled release over long period of time in comparison to oral marketed valsartan tablets. The in vitro permeation studies revealed that the strength of the three dimensional network gel structure formed on the surface of the backing layer played a major role in the drug release. Combining sodium alginate with carbopol-934 created a weak gel structure that enhanced the drug release, whereas, the combination of HPMC with carbopol-934 created a strong gel structure that retarded the drug release. FTIR and DSC studies confirmed the postulated intermolecular interaction between the drug and the polymers which controlled the gel strength and consequently the drug release.